2011
DOI: 10.1371/journal.pntd.0001150
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Staphylococcus aureus from Remote African Babongo Pygmies

Abstract: BackgroundPandemic community-acquired methicillin-resistant Staphylococcus aureus isolates (CA-MRSA) predominantly encode the Panton-Valentine leukocidin (PVL), which can be associated with severe infections. Reports from non-indigenous Sub-Saharan African populations revealed a high prevalence of PVL-positive isolates. The objective of our study was to investigate the S. aureus carriage among a remote indigenous African population and to determine the molecular characteristics of the isolates, particularly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
54
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 46 publications
14
54
1
Order By: Relevance
“…50%) [61,62]. Interestingly, the genetic background ST121, t159, agrIV (CC121) was found among isolates from healthy carriers in Asturias and from a remote African pygmy in Gabon, but the African isolate harboured lukPV [63]. Due to the common genetic background, there is a certain risk for European MSSA to acquire the PantoneValentine leukocidin genes.…”
Section: Discussionmentioning
confidence: 99%
“…50%) [61,62]. Interestingly, the genetic background ST121, t159, agrIV (CC121) was found among isolates from healthy carriers in Asturias and from a remote African pygmy in Gabon, but the African isolate harboured lukPV [63]. Due to the common genetic background, there is a certain risk for European MSSA to acquire the PantoneValentine leukocidin genes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that PVL + MSSA, often detected at high frequency in parts of Africa, may have acted as a reservoir for CA-MRSA [80, 81]. The emergence of methicillin-resistance is to not exclusively linked PVL-positive MSSA as for example USA300 appears to have evolved from a USA500 progenitor where the acquisition of PVL was one of the last steps in this process [82].…”
Section: Case Studiesmentioning
confidence: 99%
“…The nasal S. aureus carriage in the remote indigenous Gabonese Babongo Pygmies was about 30 % and no MRSA was detected [81]. ST30 was most common (24 %) among the ten diverse sequence types, which also included ST15, ST72, ST80, and ST88 (Table 2) and more than half of all isolates carried PVL.…”
Section: Case Studiesmentioning
confidence: 99%
“…7 This further supports the 'out of Africa' hypothesis of certain pandemic S. aureus clones, which have been found in remote African Pygmy populations. 8,9 Indeed, the major European community-acquired PVL-positive methicillin-resistant S. aureus (ST80 CA-MRSA) most likely originated from Sub-Saharan Africa, as revealed by whole genome sequencing analyses. 10 In conclusion, the study by Rosenthal et al and our report point towards the significance of migration in the spread of certain pathogens such as S. aureus.…”
mentioning
confidence: 99%